Assessment Study: The Economic Cost of Integrated School Gardening in School Feeding Program - Phuong Vichea, Vanna; Sockcheng, Sim; Sombath, KEO (WorldFish, 2024)
This study evaluates the economic and nutritional impacts of integrating school-grown gardens into Cambodia’s school meals program during the 2022-2023 academic year, using a mixed-methods approach. State-run schools were the most cost-efficient, with an annual cost of USD 38.90 per student, compared to USD 55.24 in WFP-run schools due to higher infrastructure investments. Gardening schools, costing USD 53.08 per student, generated USD 600–900 annually from surplus vegetable sales. Nutritional analysis revealed significant deficiencies across all models, with breakfasts providing only 228.82 kcal on average, well below the recommended 360 kcal. Macronutrients and key micronutrients, including calcium, iron, and vitamins A and C, were inadequate, posing risks to students’ cognitive and physical development.